Quantum Heat Flow Model for Heat Flow in Some Nanotubes - Mohamed, Muhanad Elfadil; A. Allah, Mubarak Dirar; Fadol, Asim Ahmed Mohamed; Rashed, Mohammed Margani; M . A . Mahmoud, Hassaballa; AbdAlgadir, Lutfi Mohammed; Ahmed, Zoaloon; Mohamed, Abd Elazeem (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Using Schrodinger equation in a fractional medium a useful expression for heat flow through Nano tubes has been found. Fortunately, this equation resembles that obtained by Moran Wang etal, and Hai- Dong Wang teal. the ordinary thermal conductivity is constant. The effective thermal conductivity temperature dependent resembles that obtained for carbon Nano tubes and Boron Nitride Nano tubes. It is also finite at low temperature which also conforms with experimental data for carbon and Boron. Since Nano materials are described by quantum lows, this new model is thus more suitable for Nano tubes, as for as it is derived using quantum laws.